Mycelial frontiers: harnessing fungal morphological superiority and enzymatic versatility for deep-soil crude oil restoration in the Niger Delta - Shuaib, Maryam Eyya; Thakur, Aman; Parra-Saldívar, Roberto; Coulon, Frederic; Medina, Angel (Frontiers, 2026)
The extensive environmental degradation resulting from decades of crude oil contamination in the Niger Delta necessitates a critical re-evaluation of current restoration strategies. This crisis has persistently impacted soil and water resources, decimated mangrove forests, and undermined the socio-economic stability of local communities. An appraisal of current remediation efforts reveals a significant performance gap, with conventional techniques proving inadequate for the region's unique environmental conditions and the sheer depth of contamination. This review critically assesses the potential of mycoremediation in aerated environments as a superior, ecologically congruent alternative. We explore the distinct morphological and metabolic advantages of fungi over bacteria, particularly the ability of filamentous mycelial networks to penetrate and colonize deep soil matrices, thereby overcoming the critical depth limitations of existing methods. The paper investigates dual mechanisms of fungal action: potent enzymatic degradation via non-specific extracellular enzymes and non-enzymatic biosorption of pollutants. Furthermore, it analyzes how key environmental modulators in the Niger Delta, specifically acidic pH, mesophilic temperatures, and fluctuating water potential naturally select for fungal dominance. The review concludes by advocating for a paradigm shift away from generic microbial solutions toward bioprospecting and cultivating potent, indigenous fungal strains pre-adapted to local contaminants. Ultimately, this paper frames mycoremediation as a low-cost, decentralized technology capable of empowering communities, restoring livelihoods, and advancing environmental justice in this critically polluted region.
Keywords: 3107 Microbiology; 3207 Medical microbiology; bioprospecting; crude oil; Lignin-Modifying Enzymes (LMEs); mycoremediation; Niger Delta